KESESUAIAN LAHAN UNTUK JENIS CENDANA (SANTALUM ALBUM LINN.) DI KABUPATEN ALOR PROVINSI NUSA TENGGARA TIMUR - Kurniawan, Hery; Sumardi, Sumardi; Pujiono, Eko (Bumi Lestari, 2016)
Cendana (Santalum album L.) is an indigenous species of east nusa tenggara (Nusa Tenggara Timor/NTT) which has high economies value. The existency of this species in nature has almost extinct due to uncontrolled exploitation. It needs conservation and development efforts. The efforts needs data of land suitability endorsement to support the success of plantation. This research was aimed to set land suitability digital map for cultivating cendana as guidance in making plan cendana plantation in Alor Regency. The research used land suitability analysis method  by field survey. Purposive sample was determined based on land variation by land cover and type of soil. The result showed the large of land suitability 2 is the largest with 126.810,73 Ha, followed by land suitability 1 with 58.893,2 Ha large of area, then land suitability 4 with 20.011,41 Ha, and land suitability 3 with 5.664,58 Ha large of area.
Keywords: Alor, land suitability, map, Cendana